PENGARUH PENDANAAN INTERNAL DAN KEMAMPULABAAN TERHADAP PERTUMBUHAN PERUSAHAAN (Studi Kasus pada PT. Timah Tbk. dan PT. Aneka Tambang Tbk.) - ., Jeffry (Jurnal Ilmiah Binaniaga, 2011)
The objective of this research is to understand the influence of retained earning and profitability to the growth of the company, to know the significance internal fund and profitability to the growth of the company with partial and  to know the significance internal fund and profitability to the growth of the company with simultant. Projection that is used for internal fund is retained earning, profitability is return on equity (ROE), and the growth of the company is growth (g). Data used are the two mining companies for 5 years starting from 2004 until 2008Analysis methods used are coefficients correlation for the relationships between the variables, coefficients determination to measure the closeness relationship among the variables, regression coefficients to measure the influence of the free variables are bound variables, and ratio analysis to determine the size of the portion of each variable. Results of research on PT Timah Tbk and PT Aneka Tambang Tbk is (a) for t test internal fund with proxy retained earnings has a significant influance to the growth of the company with proxy growth, (b) for t test profitability with proxy return on equity doesn’t has a significant influance to the growth of the company with proxy growth, and (c) for f test internal fund with proxy retained earnings and profitability with proxy return on equityhas a significant influence to the growth of the company with proxy growth. Keywords : internal fund,  profitability, growth of the company